Respostas
respondido por:
10
x² = 8x - 15
x²-8x + 15 = 0
delta = (-b)² - 4 .a .c
delta =(-8)² - 4 . 1 . 15
delta= 64 -60
delta = 4
x= - b =/- Vdelta(raiz de delta)/2.a
x= - (-8) +/-V4/2.a
x= 8 +/-2 /2
x' = 8 + 2/2
x' = 10/2
x' = 5
x'' = 8 - 2/2
x'' = 6/2
x'' = 3
x²-8x + 15 = 0
delta = (-b)² - 4 .a .c
delta =(-8)² - 4 . 1 . 15
delta= 64 -60
delta = 4
x= - b =/- Vdelta(raiz de delta)/2.a
x= - (-8) +/-V4/2.a
x= 8 +/-2 /2
x' = 8 + 2/2
x' = 10/2
x' = 5
x'' = 8 - 2/2
x'' = 6/2
x'' = 3
d3xter:
obg cara!!!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás